ANALISIS SOSIAL EKONOMI DAN BUDAYA MASYARAKAT PESISIR KAMPUNG NELAYAN SEBRANG - Putra, Ilham Mirzaya; Irawan, Fikry; Alifsyah, M.; Effendy, M. Ridho; Tanjung, Rizky Nabila; Patricia, Vica Lily Tan (Universitas Islam Negeri Raden Intan Lampung, 2022)
The purpose of this study was to find out how the economic and cultural development of the coastal community of Kampung Nelayan Seberang. The research method used is a case study method through a qualitative approach. Data collection techniques through interviews, observations of coastal community life and documentation. Data analysis was carried out through several stages, namely data reduction, data display and conclusion drawing. The results of the study show that the economy of the Masyaakat Kampung Nelayan is largely supported by the capture fisheries sector which is strongly influenced by the weather, while the number of family dependents is quite large. In addition, the absence of markets and refueling stations has disrupted mobility and trade distribution routes. From a cultural perspective, the fishing village community is multi-ethnic. The interactions that occur between residents are supported by the existence of houses that are quite close together, the similarity of livelihoods, and community ownership together. Community empowerment programs need to be carried out so that the Kampung Nelayan area is growing and prosperous.